Integrating Good Corporate Governance, Islamic Corporate Social Responsibility, Zakat, Syariah Governance, and Syariah Compliance: Exploring their Interconnected Impact on the Financial Health of Islamic Commercial Banks - Solihati, Garin Pratiwi; Suhardiyanto, Herry; Hakim, Dedi Budiman; Irawan, Tony (PT. LITERASI SAINS NUSANTARA, 2023)
The background of this research revolves around the need to understand the complex relationship between Good Corporate Governance (GCG), Islamic Corporate Social Responsibility (ICSR), zakat, Shariah Governance (SG), and Shariah Compliance (SC) in the context of financial institutions, particularly Islamic banks. This study adopts a holistic framework to explore their interconnected impacts on the financial health of Islamic banks. The research utilized a comprehensive literature review with qualitative analysis, aiming to gain a thorough understanding of the subject from 2010 to 2023. The findings indicate that in the face of business complexity and global market dynamics, Islamic banks need to implement concepts such as Good Corporate Governance (GCG), Islamic Corporate Social Responsibility (ICSR), Zakat, Shariah Governance (SG), and Shariah Compliance (SC). The holistic integration of these principles can have a significantly positive impact on the financial health of Islamic banks. GCG provides a robust foundation for risk management and transparency, ICSR enriches the social and environmental dimensions, Zakat plays a crucial role in wealth redistribution and community economic empowerment, while SG and SC ensure adherence to Shariah principles and maintain the integrity of financial institutions. By effectively applying these concepts, Islamic banks can strengthen their position in facing market challenges and enhance their contributions to sustainable economic development.